Analisis Manajemen Risiko Berbasis ISO 31000, SWOT dan Matriks Risiko Pada Supermarket Yogya Kopo Mas Bandung - Yesica Maulina; Ashilah Fauziyah; Siti Azmi Nur Islami; Umu Mahmudah; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze, evaluate, and provide risk treatment recommendations for Yogya Kopo Mas Supermarket in Bandung using an integrated approach involving ISO 31000, SWOT strategic analysis, and the risk matrix. This descriptive qualitative research collected primary data through management interviews and field observation. The SWOT analysis results generated four combined strategies (S-O, W-O, S-T, W-T) that served as the foundation for risk treatment. Through the ISO 31000 risk management process, 36 risk events were successfully identified and grouped into seven categories. The risk assessment using the Risk Matrix indicated that six events were at a High-risk level: Product damage/expiration (R03), Major equipment failure (R05), Inventory loss due to theft (R10), Decline in consumer purchasing power (R25), Modern retail competition (R28), and UMR increase (R29). Meanwhile, 25 risks were categorized as Medium and 5 as Low. The study recommends mitigation actions based on the combined SWOT strategies and prioritized for the six High risks, including tightening FIFO/FEFO implementation, routine equipment maintenance, and strengthening store security, to ensure the sustainability of supermarket operations.